Bioinspired Strategies for Functionalization of Mg-Based Stents - Feng Wu; Yixuan Liu; Jingan Li; Kun Zhang; Fali Chong (Crystals, 2022)
Magnesium alloys have attracted considerable interest as prospective biodegradable materials in cardiovascular stents because of their metal mechanical properties and biocompatibility. However, fast degradation and slow endothelialization results in the premature disintegration of mechanical integrity and the restenosis of implanted Mg-based stents, which is the primary hurdle limiting their predicted clinical applicability. The development of bioinspired strategies is a burgeoning area in cardiovascular stents’ fields of research. Inspired by the unique features of lotus leaves, pitcher plants, healthy endothelial cells (ECs), marine mussels, and extracellular matrix, various bioinspired strategies have been developed to build innovative artificial materials with tremendous promise for medicinal applications. This perspective focuses on bioinspired strategies to provide innovative ideas for reducing corrosion resistance and accelerating endothelialization. The bioinspired strategies are envisaged to serve as a significant reference for future research on Mg-based medical devices.